Fungsi Dan Peran Media Masa Dalam Film Habibie Ainun (ANALISIS SEMIOTIKA Roland Barthes) - Gibran, Feriel; Zein, Shofia; Kulsum, Ummi; Wijayani, Qoniah Nur (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study analyzes the semiotics of the role and function of mass media in Habibie Ainun's films. This story is taken from the real life of a young man named Baharudin Jusuf Habibie who tried to build the Indonesian aerospace industry and make airplanes. The purpose of this study is to find out how the moral message conveyed in Rudy Habibie's film shapes moral messages such as human relationships with others, God, and their social environment. Using the k approach Myths, on the other hand, explain the habits and beliefs of the general public. The study divides the scene into three parts: man's relationship with man, man's relationship with God, and man's relationship with the social environment. Each section consists of eleven simple scenes. Data collection identifies the corpus of subtitles according to the classification found. The results of the research can be shown by the existence of mass media through this film will have a good impact on the community, especially for teenagers who can be innovated towards the main character who is memorable to bring many examples of good moral values that can be applied in everyday life and at the same time can boost the life of a more advanced nation.